Lecture by Antonio Carlos Robert de Moraes: BASES DA FORMAÇÃO TERRITORIAL DO BRASIL - Moraes, Antonio Carlos Robert (Geografares, 2020)
This text originated from a lecture that was transcribed and then revised by Tonico, as Antonio Carlos Robert de Moraes was affectionately known, and published in number 2 of Geografares. The lecture was delivered at the seminar on Pensamento Geográfico e Formação Territorial do Brasil [Geographical Thought and Territorial Formation in Brazil], organized by the Associação dos Geógrafos Brasileiros [Associação of the Brazilian Geographers] (AGB), Vitória Section, and by the Department of Geography of the Universidade Federal do Espírito Santo [Federal University of Espírito Santo], on December 8, 2000.